Formation of the State-Religion Relations in Ancient Azerbaijan - Mammadov, Jeyhun (Scholarya Demo Journal of Ruby, 2022)
This article covers the relations between state and religion existing in ancient Azerbaijan. It is noted that a specific state religious policy was pursued on the territory of Mannea, Media, Atropatene, and Caucasian Albania in ancient times. It is well to bear in mind that contradictions between the ancient religious and legal norms of the Avesta and the socio-economic conditions in the feudal Sasanian Empire existed in ancient Azerbaijan. The strongly-pronounced scholastic and conservative nature of theology in the Sassanid Empire manifested itself amid its active military and trade expansion. The population residing on the lands of the Sassanid Empire practiced different religions and represented various cultures, as well as levels of social and economic development. The official religious structures of the empire were forced to accept the presence of the schools of thought studying the legacy of Aristotle and teaching Christianity on their territory. The religious establishment of Zoroastrianism had to reckon with the influence of religion and culture of India, putting up with the study of the Middle Persian translation of the Avesta, the basics of the philosophical teachings of the "Greeks", as well as ancient Indian philosophy and medicine. Zoroastrianism had been the main religion for the ancient tribes of Azerbaijan, Iran and Central Asia since the Achaemenid dynasty. Later, it has become widespread in other regions. Its priests claimed that the existing social order has a divine origin. Zoroastrianism, being the religion of ancient Azerbaijan, played an essential role in the relations between State and religion of the day. It was reflected in the state policy. The teachings of Zoroastrianism at a later stage influenced ancient Greek and European philosophy, as well as consciousness, lifestyle and behavior in the territories where it was widespread as a dualistic philosophical system and moral code. At that time, the heads of state established influential and powerful Zoroastrian structures (magustan) in every city. Zoroastrianism prevailed as the state religion in the palace, in all cities and territories of the country.